Técnicas de concentración en el mejoramiento de la comprensión de textos escritos en inglés en estudiantes de tercer grado de secundaria de la Institución Educativa Secundaria Pública 60052 Generalísimo José de San Martín de Punchana 2023 - Ahuanari Vela, Winder Hernan (2025)
The study aimed to evaluate the effectiveness of concentration techniques in improving English text comprehension among third-grade students at the Generalísimo José de San Martín de Punchana Secondary Public Educational Institution in 2023. The research was evaluative in nature, employing a field study, contemporary transectional, univariate, quasi-experimental designs. The study population consisted of 267 individuals, with a sample of 44 students divided into two groups. The average results for both groups were 10.2 for the experimental group and 7.5 for the control group in a scale of 0-20, indicating that both groups were in the beginner category. However, upon comparing these findings, statistical significant differences in the post-test were observed, as the p-value was 0.000, which is less than α = 0.05, confirming that the learner-training program was effective at improving the sample students’ reading skills.